Trajectories of functional and structural myocardial parameters in post-COVID-19 syndrome—insights from mid-term follow-up by cardiovascular magnetic resonance - Gröschel, Jan; Grassow, Leonhard; van Dijck, Phillip; Bhoyroo, Yashraj; Blaszczyk, Edyta; Schulz-Menger, Jeanette (Frontiers in Cardiovascular Medicine, 2024)
In total 43 patients (median age (IQR) 46(37-56) years, 33 females) received follow-ups 347(167-651) days after initial diagnosis. A decrease in symptoms was recorded on follow-ups (p<.03) with 23 patients being asymptomatic at follow-up (symptomatic at baseline 43/43 (100%) vs. symptomatic at follow-up 21/43 (49%), p<.001). Functional improvement was noted for LV-SV (83.3 (72.7-95.0) vs. 84.0 (77.0-100.3) ml; p=.045), global radial (25.3 % (23.4-27.9) vs. 27.4 % (24.4-33.1); p<.001) and circumferential strains (-16.5 % (-17.5-(-15.6)) vs. -17.2 % (-19.5-(-16.1)); p<.001). In total N=17 patients had a LV-SV change >10% on follow-up scans (5 with a decrease and 12 with an increase), with LV-SV, RV-SV and global longitudinal strain being discriminatory variables on baseline scans (p=.01, .02 and .04, respectively). T1-or T2-analysis revealed no changes, remaining within normal limits.Symptomatic load as well as blood pressures decreased on follow-up. CMR did not detect significant changes in tissue parameters, however volumetric, specifically LV-SV, and deformation indices improved during mid-term follow-up.